2018
DOI: 10.12732/dsa.v27i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Maximum Likelihood Estimation in Nonlinear Nonmarkov Diffusion Type Processes

Abstract: ABSTRACT:We obtain the strong consistency, uniform asymptotic normality and local asymptotic minimaxity (in the Hajek-LeCam sense) of the two stage sequential maximum likelihood estimator of a parameter appearing nonlinearly in the drift coefficient of a stochastic differential equation when the corresponding non-Markov diffusion type process is observed until the observed Fisher information of the process exceeds a predetermined level of precision and the level becomes large. Main results are illustrated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…With θ = 0, the process is nonstationary and satisfies the LABF (local asymptotic Brownian functional) property. For all θ ∈ R, the model satisfies the LABF property, see Bishwal [9] for the definitions of these LAN, LAMN and LABF properties. Bishwal [9] has shown that sequential sampling based on a stopping rule unifies the three properties and makes them LAN.…”
Section: Discussionmentioning
confidence: 99%
“…With θ = 0, the process is nonstationary and satisfies the LABF (local asymptotic Brownian functional) property. For all θ ∈ R, the model satisfies the LABF property, see Bishwal [9] for the definitions of these LAN, LAMN and LABF properties. Bishwal [9] has shown that sequential sampling based on a stopping rule unifies the three properties and makes them LAN.…”
Section: Discussionmentioning
confidence: 99%
“…While in Gaussian OU case, for different parts θ > 0, θ < 0 and θ = 0, LAN, LAMN and LABF hold respectively (see Bishwal [11]), in stable case entirely different phenomena occur.…”
Section: Equivalence Of Transition Probabilitiesmentioning
confidence: 99%